Alterações fenotípicas em células dendríticas induzidas por exossomos alogênicos - Hama, Rebeca Sayuri Salvucci [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
Nanovesicles such as exosomes (Exo) result from the fusion of multivesicular bodies with plasma membrane and are involved in the intercellular communication. It makes Exo an attracting tool for increasing the immunogenicity of dendritic cells (DCs), since they can transfer tumor antigens to other DCs to induce tumor-specific T lymphocytes. Therefore, we hypothesize that the sensitization of DCs with allogeneic Exo not only altered their phenopyte, but also that of the Exo they secrete. Thus, monocytes of HLA-A2+ healthy donors were differentiated to DCs with GM-CSF and IL-4 for 7 days. At the 6th day, DCs were pulsed with PSA peptide, and IL-1, IL-6, TNF- and PGE2 were added to the culture. DC culture supernatant was ultracentrifuged and filtrated for the isolation of exosomes (Exo-A2+), which were used to sensitize DCs from HLA-A2- healthy donors. At the 5th day of differentiation these DCs (HLA-A2-) were pulsed with prostate specific antigen (PSA) protein. After 18 hours, DCs were pulsed with Exo-A2+ (10g/106 DCs) and activated (IL-1, IL-6, TNF- and PGE2) for 24 h. Phenotypic analysis by flow cytometry showed that DCs treated with Exo-A2+ present high number of CD14+ cells than DCs HLA-A2+. Analysis of molecules involved with lymphocyte activation shows that DCs-Alo treated with Exo-A2+ present an increase expression of CD86 molecules, but, HLADR, CD80 and CD83 molecules expression were low. These results do not seem to be due to treatment with allogeneic Exo, since DCs A2- of control groups presented the same profile of response, indicating that the haplotype difference may have influenced the phenotype changes. This decreased expression also reflected on exosomes from DC A2- (Exo-Alo), which present low expression of typical exosomes markers, such as CD9, CD81 and CD63. In conclusion, our results show that the treatment with allogeneic Exo does not increase the immunogenicity of DCs or of their Exo, and that differences of among...

Nanovesículas como os exossomos (Exo) resultam da fusão de corpos multivesiculares com a membrana plasmática e estão envolvidos na comunicação intercelular. Os Exo são uma atrativa ferramenta para aumentar a imunogenicidade de células dendríticas (DCs), uma vez que eles podem transferir antígenos tumorais para outras DCs para induzir a geração in vivo e in vitro de linfócitos T tumorespecíficos. Sendo assim, hipotetizamos que DCs sensibilizadas com exossomos alogênicos (Exo-A2+) podem mudar seu fenótipo, assim como o dos Exo por elas secretados (Exo-Alo). Para tanto monócitos de doadores saudáveis HLA-A2+ foram diferenciados em DCs na presença de GM-CSF e IL-4 por sete dias. No sexto dia de cultura, as DCs foram pulsadas com o peptídeo PSA-1 e ativadas concomitantemente com IL-1, IL-6, TNF- e PGE2. O sobrenadante da cultura de DCs foi ultracentrifugado e filtrado para isolar os exossomos (Exo-A2+), que foram então utilizados para sensibilizar DCs de doadores saudáveis HLA-A2-. No quinto dia de diferenciação estas DCs (HLA-A2-) foram pulsadas com proteína PSA e após dezoito horas foram tratadas com Exo-A2+ (10g/106 DCs) e ativadas (IL-1, IL-6, TNF- e PGE2) por vinte e quatro horas. Análises fenotípicas por citometria de fluxo mostraram que as DCs tratadas com Exo-A2+ apresentaram maior número de células CD14+ que as DCs HLA-A2+. A análise da expressão das moléculas envolvidas com ativação linfocitária demonstrou que as DCs-Alo tratadas com Exo- A2+ apresentaram maior expressão da molécula CD86, no entanto, a expressão das moléculas HLA-DR, CD80 e CD83 apresentaram-se em menor densidade. Esses resultados parecem não ser apenas decorrente do tratamento com Exo alogênico, uma vez que as DCs A2- dos grupos controles apresentaram o mesmo perfil de resposta, indicando com isso que a diferença de haplótipos pode ter influenciado no fenótipo observado. Essa diminuição de expressão também refletiu nos..
Phenotipic alterations induced by allogeneic exosomes on dendritc cells
Keywords: Imunoterapia; Antigenos; Exossomos; Próstata - Câncer; Células cancerosas; Imunidade (Higiene); Cancer cells